The relationship between stock market development and economic growth: a case of South Africa - Ndima, Zanele (My University, 2021)
The association between the growth in the economy and development of the stock market has fascinated the attention of several economists and researchers across the world. This area of research has predominantly been performed through panel studies. However, the institutional differences and capital allocation differences between economies makes it challenging to generalise the results. Therefore, there is a need for country specific studies. This research examines the causal connection between the expansion of the equities market (Johannesburg Stock Exchange) and the advancement in the economy from a South African perspective. The research study first establishes the presence of a cointegration relation between the stock market development and economic growth. Secondly, the study explores the ultimate direction of the causal relationship. The outcomes of the Johansen cointegration assessment reveal that the proxies used for stock market development does not affect economic growth except for the number of stocks traded. Using the causality test, the study discovered the existence of a unidirectional causality from stock turnover to growth in the economy. As such, policy makers should focus on developing policies and strategies that promote the liquidity of the stock exchange because it influences the growth in the economy. Originality was incorporated in the research paper by focusing on the period between 2000 and 2019. Since most of the empirical studies examining the association between the expansion of the stock market and advancement in the economy employed panel data, this research employs a time series data, with a concentration on South Africa.
A thesis submitted to the Wits Business School, Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in Finance and Investment0, 2021
Keywords: Stock Market Development; Economic Growth; South Africa; Johannesburg Stock Exchang; SDG-8: Decent work and economic growth